Male Incarceration, the Marriage Market, and Female Outcomes - Charles, Kerwin Kofi; Luoh, Ming Ching (The Review of Economics and Statistics, 2010)
This paper studies how rising male incarceration has affected women through its effect on the marriage market. Variation in marriage-market shocks arising from incarceration is isolated using two facts: the tendency of people to marry within marriage markets defined by the interaction of race, location, and age and the fact that increases in incarceration have been very different across these three characteristics. Using a variety of estimation strategies, including difference and fixed effects models and TSLS models in which we use policy parameters to instrument for within-marriage market changes in incarceration, we find evidence that is, on the whole, consistent with the implications of the standard marriage-market model. In particular, higher male imprisonment appears to have lowered the likelihood that women marry, modestly reduced the quality of their spouses when they do marry, and shifted the gains from marriage away from women and toward men. The evidence suggests that women in affected markets have increased their schooling and labor supply in response to these changes.